Employee Types and Endogenous Organizational Design - Antoni Cunyat; Randolph Sloof (Tinbergen Institute, 2008)
When managers are sufficiently guided by social preferences, incentive provision through an organizational mode based on informal implicit contracts may provide a cost-effective alternative to a more formal mode based on explicit contracts and monitoring. This paper reports the results from a laboratory experiment designed to test whether organizations make full effective use of the available preference types within their work force when drafting their organizational design. Our main finding is that they do not do so; although the importance of social preferences is recognized by those choosing the organizational mode, the significant impact managers' preferences have on the behavior of workers in the organization seems to be overlooked.
Keywords: C91; J40; M50; 330; Organizational design; social preference types; experiments; Organisationsstruktur; Humanressourcen; Verhalten in Organisationen; Test